Sequencing of Transcriptome and Small RNA Revealed the Xenobiotic Metabolism-Related Genes and Potential Regulatory miRNA in Asian Tramp Snail - Yang, Qun; Yang, Wanjun; Shang, Feng; Ding, Biyue; Niu, Jinzhi; Wang, Jinjun (Frontiers in Genetics, 2021)
The Asian tramp snail, Bradybaena similaris (Ferusssac), is an invasive land snail species and has been a rising agricultural pest in south of China. As a pest, it also plays a role in transmission of Angiostrongylus cantonensis. However, present studies on this species are rare and the molecular information is limited. For this purpose, we sequenced the transcriptome and small RNA of B. similaris collected from citrus orchards. In total, 89,747 unigenes with an N50 size of 1287 bp and an average length of 817 bp were generated from ∼8.9 Gb transcriptome and 31 Mb clean reads were generated from ∼36 Mb small RNA library. To demonstrate the usefulness of these two datasets, we analyzed a series of genes associated with xenobiotic metabolism and core RNAi machinery. Analysis of the transcripts resulted in annotation of 126 putative genes encoding cytochrome P450 monooxygenases (CYP, 45), carboxyl/cholinesterases (CCE, 13), glutathione-S-transferases (GST, 24), and ATP-binding cassette transporters (ABC, 44). Analysis of the small RNA detected 42 miRNAs. In addition, four genes involved in small RNA pathways (miRNA, piRNA, and siRNA) were identified, and a total of 430 genes that can be targeted by miRNAs were predicted. Moreover, we found that a few miRNAs could target certain genes involved in xenobiotic metabolism. Therefore, we believe that these two datasets and the characterization of the identified/predicted genes will facilitate the molecular study of this species as well as other land snails with agricultural importance.